Kindergarten in the Digital Era: Developing Engaging Android-Based Educational Tools for Letters and Numbers - Hapsari, Estuning Dewi; Kurniawati, Inung Diah; Setiawan, Kodrat Eko Putro; Mahendra, Muhammad Isya Noor (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
The rapid advancement of technology has revolutionized educational methodologies, particularly in early childhood education. This study focuses on the development of interactive learning media for kindergarten students, aimed at facilitating the understanding of letters and numbers. Employing the ADDIE model, this developmental research was conducted at Cahaya Wonoasri Kindergarten, Madiun. Data collection involved observation, interviews, and questionnaires, targeting content validity, learning design, and media efficacy. The study culminated in the creation of an Android-based application, designed to be engaging for young learners. The application's effectiveness was validated through expert assessments and individual trials, demonstrating its potential in improving letter and number recognition among kindergarten students. The content, learning design, and media experts rated the application as 'good' to 'very good' in their respective areas of expertise. The findings suggest that the developed educational tool is not only viable but also beneficial in enhancing the learning experience for kindergarten children. The application's engaging design and interactive content align with modern teaching methodologies, potentially setting a new standard in early childhood education technology. This study highlights the significance of integrating technology in early education, especially in the digital era. The success of the developed Android-based application suggests a promising future for digital learning tools in kindergarten, potentially revolutionizing the way young children are introduced to fundamental concepts like letters and numbers.